Housing a Heretic: Johannes Oecolampadius (1482-1531) and the Pre-History' of the Servetus Affair - Fisher, Jeff (Reformation & Renaissance review, 2018)
Although many scholars have written about Calvin's treatment of Michael Servetus, very few have explored Servetus's earliest encounters with other Protestant Reformers. By utilizing letters, prefaces and other writings in the sixteenth century, this study aims to develop a portrait of the multiple ways in which the Basel Reformer, Johannes Oecolampadius, influenced Servetus and ultimately, the outcome of his trial. Perhaps most notably in the background of the Servetus affair, Oecolampadius allowed Servetus to live in his house for 10 months prior to the publication of his first antitrinitarian book. The correspondence between the two of them, and the correspondence between Oecolampadius and other Reformers in 1530-1531, enables us to fill out the picture of Servetus's early ideas and reactions to them. The descriptions of events more than 20 years later in Geneva likewise aid our understanding of Servetus's trial and the ways Oecolampadius's legacy and reputation affected it.